Hajibandeh Index versus NELA score in predicting mortality following emergency laparotomy: A retrospective Cohort Study. (June 2022) - Hajibandeh, Shahab; Hajibandeh, Shahin; Waterman, Jennifer; Miller, Bethany; Johnson, Bethan; Higgi, Adnan; Hale, Jay; Pearce, Dafydd; Evans, Louis; Satyadas, Thomas; Mansour, Moustafa; Havard, Tim; et al.
Abstract: Objectives: To compare performance of the Hajibandeh Index (HI) and National Emergency Laparotomy Audit (NELA) score in predicting postoperative mortality in patients undergoing emergency laparotomy. Methods: In compliance with STROCSS guidelines for observational studies a cohort study was conducted. All patients aged over 18 who underwent emergency laparotomy between January 2014 and January 2021 in our centre were considered eligible for inclusion. The HI and NELA indices in predicting 30-day and 90-day postoperative mortality were compared. The discrimination of each test was evaluated using Receiver Operating Characteristic (ROC) curve analysis, classification using the classification table and calibration using a plotted diagram of the expected versus observed mortality rates. Results: Analysis of 700 patients showed that the predictive performance of the HI and NELA models were comparable (30-day mortality: AUC: 0.86 vs 0.87, P = 0.557; 90-day mortality: AUC: 0.81 vs 0.84, P = 0.0607). In terms of 30-day mortality, HI was significantly better than the NELA model in predicting postoperative mortality in patients aged over 80 (AUC: 0.85 vs 0.72, P = 0.0174); however, the performances of both tools were comparable in patients with ASA status above 3 (AUC: 0.82 vs 0.82, P = 0.9775), patients with intraperitoneal contamination (AUC: 0.77 vs 0.85, P = 0.0728) and patients who needed a bowel resection (AUC: 0.85 vs 0.88, P = 0.2749). In terms of 90-day mortality, HI was significantly better than the NELA model in predicting mortality in patients aged over 80 (AUC: 0.82 vs 0.71, P = 0.0214); however, NELA had better predictive value in patients with intraperitoneal contamination (AUC: 0.76 vs 0.85, P = 0.0268); the performances of both tools were comparable in patients with ASA status above 3 (AUC: 0.77 vs 0.80, P = 0.2582), and patients who needed a bowel resection (AUC: 0.81 vs 0.86, P = 0.05). Both tools were comparable in terms of classification and calibration. Conclusions: Hajibandeh index was better than the NELA score in predicting postoperative 30-day and 90-day mortality in patients aged over 80 undergoing emergency laparotomy. Its performance in predicting 30-day and 90-day mortality was comparable with NELA score in other subgroups except 90-day mortality in patients with intraperitoneal contamination where the performance of NELA was better. We encourage other researchers to validate HI in predicting mortality following emergency laparotomy. Highlights: Hajibandeh Index (HI) is a strong predictor of postoperative mortality in patients undergoing emergency laparotomy. The performance of HI was better than the NELA score in predicting postoperative mortality in patients aged over 80. The predictive performance of both models were comparable in terms of discrimination, classification, and calibration.